Unraveling the origin of the Parnaíba Basin: Testing the rift to sag hypothesis using a multi-proxy provenance analysis - Cerri, Rodrigo I. [UNESP]; Warren, Lucas V. [UNESP]; Varejão, Filipe G.; Marconato, André; Luvizotto, George L. [UNESP]; Assine, Mario L. [UNESP] (Elsevier, 2020)
Syneclises are long-lived sedimentary basins characterized by complex subsidence and erosion histories. The premise that these geotectonic units evolve from initial rifting processes following thermal (or flexural) subsidence is widespread in the geologic sciences and, to this day, remains a controversial issue. Seeking to test this hypothesis, we proceeded a novel multi-proxy provenance study aiming to identify differences (and/or similarities) in the sedimentary signal and source areas of the Jaibaras (rift) and Parnaíba (sag) basins. We conducted a detailed analysis of trace elements geochemistry of detrital rutile grains, macroscopic gravel composition and paleocurrents from the sedimentary deposits of the Aprazível Formation (Ediacaran - Cambrian, top of Jaibaras Basin) and the Ipu Formation (Ordovician, basal unit of Parnaíba Basin). Our data reveal that important changes in source areas occurred between the end of the rifting and the beginning of the sag phase, reinforcing the hypothesis that the evolution of the Jaibaras and Parnaíba basins were not genetically related. Our results demonstrate that conglomerates of the rift sequence are predominantly composed of volcanic, sedimentary, and metamorphic angular to sub-angular clasts, pointing to diverse, nearby source areas. Contrastingly, conglomerates of the initial sag sequence have greater sedimentary maturity, with dominant rounded vein quartz clasts and other minor source contributions, which suggest distant source areas, showing a consistent paleocurrent direction towards NW. Indeed, the detrital rutile trace elements geochemistry demonstrates that the source areas of these two units were distinct, revealing an important decrease in the input of granulite facies and metamafic grains in the sag basin comparing with the rift succession. In conclusion, as well as paleomagnetic and geochronological studies, the provenance methods using a multi-proxy approach proved to be an effective and powerful technique for distinguishing modifications in the sedimentary signal between rift-to-sag sequences.
Keywords: Jaibaras basin; Parnaíba basin; Rift-to-sag evolution; Rutile; Sediment provenance; SW Gondwana